Platforms of Work, Labour, and Employment Relationship: The Grey Zones of a Digital Governance - Dieuaide, Patrick; Azaïs, Christian (Frontiers in Sociology, 2020)
Drawing on numerous case studies, the article examines the specific conditions for organising and managing the employment relationship on digital labour platforms. We show that these conditions are largely due to the disruptive nature of the process of digitising the employee–employer relationship. Digitisation replaces the employment contract of the standard employment relationship with a triangular “worker–platform–customer” relationship. In this model, the boundaries of the employment relationship become opaque and more uncertain: the bond of subordination disappears, labour law gives way to commercial law, and the figures of the employer and the employee lose institutional visibility. The article seeks to clarify the contours of this “in-between” model and proposes the notion of the “grey zone,” borrowed from geopolitics. This notion of the “employment grey zone” makes it possible to shift the researcher's perspective by focusing attention on practices and “intermediate spaces of regulation,” which are relatively autonomous and endowed with their own dynamics. This framework of analysis broadens the perspective and helps to better understand the impact on the employment relationship of new forms of governance in a context of a digital turning point. The article first returns to the notion of the “grey zone” and argues on the foundations and interest of mobilising this notion in the field of industrial relations studies. The links between digital platforms and grey zones are then examined. In particular, we show that digital governance is based on a confusion of powers between coordination and leadership. The reflection continues in a third phase with an examination of digital management practices in two areas: the control of the activity of connected workers, and the production and management of externalities resulting from the operation of platforms. The article concludes with a discussion on the heuristic value of the notion of grey zones of employment.